THE EFFECTS OF TEAM WORD WEBBING ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN PLUS RIAU IN READING COMPREHENSION - Olifvia Monica; Syofia Delfi; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find out the effect of Team Word-Webbing on the ability of the first year students of SMAN PLUS RIAU in reading comprehension. The writer used Cluster Random Sampling technique to choose the sample. For 96 students of the population, class X M.S 4 was chosen as the sample. The instrument of this research was in form of test which consisted of pre-test and post-test. The test was narrative text. The test had five texts and each text had eight questions based on reading comprehension components so there were 40 questions for each text. The writer used SPSS 16.0 Program to analyze the data. Based on the results, the t-table was higher that the t-test and the Paired Samples Correlations was 0.914 which can be interpreted as very strong. It can be concluded that there is a significant effect of Team Word-Webbing on the ability of the first year students of SMAN PLUS RIAU in reading comprehension. It is suggested that this technique being applied in teaching reading narrative text or other texts. This technique can be applied not only in senior high school level but also in junior high school level. Fresh ideas or some improvisations from further researcher are really needed to make this technique better in its used.Key Words: Effects, Team Word-Webbing, Reading Comprehension